The Impact of Perfluorooctanoic Acid (PFOA) on the Mussel Mytilus galloprovincialis: A Multi-Biomarker Evaluation - Sandra Copeto; Sara Ganço; Inês João Ferreira; Didier Sanchez; Maria João Nunes; Carla Motta; Marco Silva; Mário Diniz (Oceans)
Perfluorooctanoic acid (PFOA) has been widely studied due to its environmental persistence and bioaccumulation potential, raising concerns about its effects on aquatic life. This research evaluates the impact of PFOA on the antioxidant defenses and stress response systems of the mussel Mytilus galloprovincialis. Mussels were exposed to three concentrations of PFOA (1, 10, and 100 µg·L−1) over 28 days. Several biomarkers, including glutathione S-transferase (GST), superoxide dismutase (SOD), catalase (CAT), lipid peroxidation (LPO), total antioxidant capacity (TAC), vitellogenin (VTG), ubiquitin (UBI), and caspase-3 (CASP) were analyzed. The results suggest stress responses, particularly in animals exposed to higher concentrations, as shown by GST and SOD activities which increased according to PFOA concentrations. Additionally, oxidative stress markers such as MDA and CAT showed variable responses depending on the exposure concentration tested. This study underscores the need for further investigation into the effects of PFOA on mollusks but also the need to unveil gender-specific responses in aquatic organisms exposed to this contaminant. The concentrations of PFOA used in our research are lower than those examined in previous studies, providing crucial insights into the impacts of even minimal exposure levels. It highlights the potential of M. galloprovincialis as a bioindicator in environmental monitoring programs, providing crucial insights for environmental management and policymaking regarding regulating and monitoring PFOA in marine settings. Consequently, in a country where seafood consumption is the second largest in Europe, implementing environmental policies and regulatory measures to manage and monitor PFOA levels in marine environments is crucial.